2011
DOI: 10.1002/ajmg.a.34350
|View full text |Cite
|
Sign up to set email alerts
|

A patient with a mild holoprosencephaly spectrum phenotype and heterotaxy and a 1.3 Mb deletion encompassing GLI2

Abstract: Loss-of-function mutations of GLI2 are associated with features at the mild end of the holoprosencephaly spectrum, including abnormal pituitary gland formation and/or function, and craniofacial abnormalities. In addition patients may have branchial arch anomalies and polydactyly. Large, microscopically visible, interstitial deletions spanning 2q14.2 have been reported in patients with multiple congenital anomalies and intellectual disability. We report here on a patient with a mild holoprosencephaly spectrum p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 24 publications
3
34
1
Order By: Relevance
“…Misregulation of the GLI2 (OMIM: 165230) gene could therefore lead to unfavorable developmental and pathological consequences (Hui & Angers, ). Mutations in GLI2 have been identified in patients with orofacial cleft (Bertolacini, Ribeirobicudo, Petrin, Richiericosta, & Murray, ; Mo et al, ; Simioni, Araujo, Monlleo, Maurer‐Morelli, & Gil‐Da‐Silva‐Lopes, ; Vieira et al, ), holoprosencephaly (Bear et al, ; Kevelam et al, ), and pituitary anomalies (Roessler et al, , ). Some variants of GLI2 have been detected in patients who present with cleft lip/palate by Sanger sequencing and are not in unrelated controls without orofacial cleft (Simioni et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Misregulation of the GLI2 (OMIM: 165230) gene could therefore lead to unfavorable developmental and pathological consequences (Hui & Angers, ). Mutations in GLI2 have been identified in patients with orofacial cleft (Bertolacini, Ribeirobicudo, Petrin, Richiericosta, & Murray, ; Mo et al, ; Simioni, Araujo, Monlleo, Maurer‐Morelli, & Gil‐Da‐Silva‐Lopes, ; Vieira et al, ), holoprosencephaly (Bear et al, ; Kevelam et al, ), and pituitary anomalies (Roessler et al, , ). Some variants of GLI2 have been detected in patients who present with cleft lip/palate by Sanger sequencing and are not in unrelated controls without orofacial cleft (Simioni et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, these 2 disorders belong to a continuous phenotypic spectrum, with the relatively mild forms referred to as CJS and severe cases known as HPE9 ( Table 1 ). Today, many case reports and reviews of human GLI2 defects have been made [Kevelam et al, 2012;Greally et al, 2014;Arnhold et al, 2015], and the actual spectrum of the phenotype of this syndrome has been clarified (online suppl. Table 1; see www.karger.com/doi/10.1159/000485227).…”
Section: Discussionmentioning
confidence: 99%
“…37 In addition, a case report on a patient with CPHD, cleft palate and heterotaxy used MLPA to confirm a whole GLI2 deletion first identified by array comparative genome hybridization. 38 In patients with SOD, the MLPA analysis did not detect GLI2 CNV. However, among these patients, we identified two novel GLI2 missense variants.…”
Section: Discussionmentioning
confidence: 94%
“…One previous study identified one patient with a heterozygous LHX4 microdeletion among 71 patients with CPHD that were examined for CNV by MLPA in POU1F1 , PROP1 , HESX1 , LHX3 , LHX4 and SOX3 genes . In addition, a case report on a patient with CPHD, cleft palate and heterotaxy used MLPA to confirm a whole GLI2 deletion first identified by array comparative genome hybridization …”
Section: Discussionmentioning
confidence: 99%